The Implementation of Scientific Approach-Based Project Learning Method to Stimulate The Early Child's Autonomy - NKG Galuh Andriasih; Luh Ayu Tirtayani (Journal of Psychology and Instruction, 2019)
The study aimed to find out the effect of the implementation of scientific approach - based project learning method to stimulate the early child’s autonomy skills. This study was conducting by quasi-experiment research with nonequivalent control group design. The population of the research is the whole group B TK Gugus IV Cempaka Denpasar Barat which is involving 529 children. The sample is taken randomly by using a random sampling technique. B1 group TK Sila Dharma amount to 24 children as the experimental group and B1 group TK Kumara Tunggal amount to 26 children as the control group. The data is taken by non-test techniques is observation. Data were analyzed using the t-test. Based on the result of the analysis, the average score of the experimental group (88,88) is higher than the average score of the control group (82.00). The result of the analysis using t-test with dk = 24 + 26 – 2 = 48 and α = 5% obtained t-count > t-table is 3,018 > 2,021 it means H0 rejected and Ha accepted. It means that there was a significant difference in early child autonomy between classes that were taught by the project learning method based on the scientific approach and classes that were taught by the conventional learning model. Thus, the project learning method based on the scientific approach influences to early child autonomy of group B TK Gugus IV Cempaka Denpasar Barat Academic Years 2018/2019.